2020
DOI: 10.3389/fonc.2020.568279
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Immunotherapy in the Peri-Operative Setting of Muscle-Infiltrating Bladder Cancer

Abstract: Patients with muscle-infiltrating bladder cancer (MIBC) present a high risk of postoperative recurrence and death from metastatic urothelial cancer despite surgical resection. Before the use of peri-operative chemotherapy, about half (52%) of patients undergoing radical cystectomy had had a relapse of tumor disease within 5 years of surgery. However, when peri-operative cisplatin-based chemotherapy is added to radical cystectomy for patients with MIBC it provides limited benefit in terms of survival, disease r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…PD-L1 inhibitors, Atezolizumab and Durvalumab, were both approved by FDA for the treatment of patients with inoperable or metastatic UCB progressing on platinum-based treatment with positive PD-L1 [ 39 ]. A PD1 inhibitor, Pembrolizumab, has been approved in the first-line treatment of UCB patients ineligible for cisplatin with tumor PD-L1 positive [ 40 ]. These immune checkpoint inhibitors were exhibited to have significant efficacy and bring obvious survival benefits to patients with metastatic UCB [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 inhibitors, Atezolizumab and Durvalumab, were both approved by FDA for the treatment of patients with inoperable or metastatic UCB progressing on platinum-based treatment with positive PD-L1 [ 39 ]. A PD1 inhibitor, Pembrolizumab, has been approved in the first-line treatment of UCB patients ineligible for cisplatin with tumor PD-L1 positive [ 40 ]. These immune checkpoint inhibitors were exhibited to have significant efficacy and bring obvious survival benefits to patients with metastatic UCB [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have focused on immune checkpoint molecules, such as CTLA-4 and PD-1/PD-L1, as components of new strategies for cancer therapy, and found that these molecules can significantly regulate the immune function of TICs [ 41 , 42 ]. BLCA is immune-responsive, and the efficacy and safety of immunotherapy in peri-operative settings in non-metastatic BLCA are being assessed in several trials [ 43 ]. Furthermore, m6A RNA modification is gaining increasing attention as a potential determinant of therapeutic resistance, including immunotherapy resistance within various cancers, and several lncRNAs have also been shown to affect the outcomes of immunotherapy [ 32 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a lack of threshold standardization to determine whether a tumor is 'positive' or 'negative' in terms of biomarker presence. Expression of PD-L1 is the most widely studied in the field, and a correlation between higher PD-L1 expression on tumor cells and response to ICI has been seen in other cancers [29]. In bladder cancer studies, PD-L1 expression has been linked to advanced pathological stages at the time of cystectomy, and to high mortality, which does suggest the biomarker may have a prognostic role.…”
Section: Biomarker Development and Future Directionsmentioning
confidence: 99%